2021
DOI: 10.3390/antiox10091398
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Cytoplasm and Mitochondrial Specific Hydroxyl Radical Scavengers TA293 and mitoTA293 in Bleomycin-Induced Pulmonary Fibrosis Model Mice

Abstract: Lung fibrosis is the primary pathology in idiopathic pulmonary fibrosis and is considered to result from an increase in reactive oxygen species (ROS) levels in alveolar epithelial cells. However, the exact mechanism underlying lung fibrosis remains unclear and there is no effective therapy. The hydroxyl radical (•OH) has the strongest oxidizing potential among ROS. Recently, •OH localized to the cytoplasm (cyto •OH) was reported to induce cellular senescence, while mitochondria-localized •OH (mt •OH) was repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…In the BLM-induced IPF model, ROS generation leads to progressive lipid peroxidation, which affects the reductive carbonyl compounds metabolism, DNA damages, increases collagen synthesis, and directly affects the antioxidant defense system [86]. ROS deactivation is performed by endogenous and exogenous antioxidant systems (SOD, CAT and GSH and etc.).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the BLM-induced IPF model, ROS generation leads to progressive lipid peroxidation, which affects the reductive carbonyl compounds metabolism, DNA damages, increases collagen synthesis, and directly affects the antioxidant defense system [86]. ROS deactivation is performed by endogenous and exogenous antioxidant systems (SOD, CAT and GSH and etc.).…”
Section: Discussionmentioning
confidence: 99%
“…•− dismutation, and their inability to reduce with oxidative disorders leads to the development of many pathological conditions [9]. Intracellular ROS and OS infiltration after BLM-induced pulmonary fibrosis is performed after the various antioxidants addition [86]. In accordance with previous studies [7], our results also show that the BLM application leads to a statistically significant increase in the parameters of OS damage i.e., increased lipid peroxidation (MDA) and ROS production (Figure 5), along with increased protein carbonylation.…”
Section: Discussionmentioning
confidence: 99%
“…Cell migration, positive regulation of cell proliferation, and lung development were basic BP in pulmonary fibrosis 44 . On the basis of the KEGG analysis, combined with relevant references, 45,46 we found many pulmonary fibrosis‐related pathways, such as the MAPK signaling pathway, Wnt signaling pathway, PI3K‐Akt signaling pathway, and Hippo signaling pathway enriched in DE RNAs. This result suggested that DE RNAs affected the development of pulmonary fibrosis through above BP and pathways.…”
Section: Discussionmentioning
confidence: 90%
“…Excessive ROS can damage cellular molecules, leading to DNA damage, lipid peroxidation and protein oxidation. These processes are key in the development of various diseases, including cancer and lung fibrosis ( 3 5 ). Cells contain a range of antioxidant enzymes, including superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GPx) and non-enzymatic antioxidants, such as reduced glutathione (GSH), for defense against ROS ( 6 , 7 ).…”
Section: Introductionmentioning
confidence: 99%